A Case Study on Coloured Petri Nets in object-oriented analysis and design - Barros, João Paulo (2005)
In this paper,we first demonstrate how a coloured Petri nets(CPN) model can be used to capture requirements for a considered example system, an elevator controller. Then, we show how this requirements-level CPN model is transformed into a design-level object-oriented CPN model, which is structurally and conceptually closer to class diagrams and object-oriented programming languages. The CPN models reduce the gap between user-level requirements and the respective implementation, thus simplifying the imple- mentation or code generation. Finally, we discuss the code generation from object-oriented CPN models.